Diabetic and sympathetic influences on the water permeability barrier function of human skin as measured using transepidermal water loss: A case-control study. Issue 45 (November 2017) - Han, Seung Hoon; Park, Ji Woong
Abstract : Abstract: The presence of long-standing hyperglycemic conditions has been suggested to lead to many skin problems associated with an impaired skin barrier function. However, the relationship between impaired skin barrier status and altered peripheral nervous system function has not yet been determined. The purpose of this study was to investigate the water evaporation rate as a measure of the permeability barrier function of diabetic skin and its relationship to diabetic sensorimotor polyneuropathy (DSPN) and peripheral autonomic neuropathy (PAN) using well-controlled confounding variables. This case-control study included 42 participants with chronic diabetes and 43 matched healthy controls. The diabetic group underwent a nerve conduction study and sympathetic skin response (SSR) test to confirm the presence of DSPN and PAN, respectively. Different skin regions were analyzed using the noninvasive Tewameter instrument (Courage + Khazaka Electronic GmbH, Cologne, Germany). The impacts of PAN, DSPN, age, and diabetes duration on the values of transepidermal water loss (TEWL) were each analyzed and compared between the groups. Regardless of the presence of DSPN or PAN, the TEWL values as measured on the distal extremities were significantly lower in the diabetic group than in the control group. In the diabetic group, participants with abnormal SSR test results showed decreased TEWL values in the finger, sole, and first toe, as compared with participants with normal SSR test results. In the control group, age showed a negative correlation with the TEWL values with respect to some measured regions. However, in the diabetic group, there was no significant correlation between either patient age or diabetes duration and TEWL values. The presence of a long-term hyperglycemic state can reduce the permeability barrier function of the skin, a phenomenon that might be related to the presence of an impaired peripheral sympathetic nervous system, rather than peripheral sensorimotor denervation.